Enhancement of sweet pepper photosynthesis and yield with green-to-red sunlight conversion despite reduced daily light integral - Kang, Jun Hyeun; Lee, Ju Young; Ahn, Tae In (한국원예학회, 2025)
Plants have adapted to sunlight over millions of years. However, recent research on functional covering materials has started to reveal their potential between solar spectral conversion and growth of some crops. In this study, we investigate the changes in the greenhouse light environment induced by a transparent polyethylene film (PE) and a green-to-red light conversion film (LCF) on the photosynthetic capacity, growth, and yield enhancement of sweet pepper (Capsicum annuum L. cv. Mavera). During the cultivation period, the average daily light integral (DLI) of the LCF was 21.1 mol m- 2 d- 1, which was 9.4% lower than that of the PE. Despite the reduction in DLI, plants grown under the LCF showed a significant increase of 25% and 36.8% in shoot and fruit dry weight per plant, respectively, compared to PE. In addition, the cumulative fruit yield per unit area under LCF was increased by 29% compared to the PE. Measurements of photosynthetic capacity in different leaf positions showed significant improvements in the upper and lower leaves with LCF treatment. Therefore, we conclude that despite the decrease in DLI resulting from the adjustment of the solar spectrum by LCF, the photosynthetic mechanisms in sweet peppers were enhanced, leading to an increase in yield.